2016
DOI: 10.1155/2016/8792725
|View full text |Cite
|
Sign up to set email alerts
|

Styloid Process of the Temporal Bone: Morphometric Analysis and Clinical Implications

Abstract: Objective. To evaluate measures of the styloid process (SP) in Brazilian dry skulls. Methods. This study involves measurements of two points (lateral end posterior views) of 15 dry skulls held by the Morphology Department, Institute of Biological Sciences of Federal University of Minas Gerais. Results. There was a large variability for the length of left and right sides (in lateral and posterior views) of the styloid process. From the lateral view of the left and right styloid, the length of the SP ranged, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…This finding was in accordance with Bozkir et al,19 Vadgaonkar et al,22 Roopashri et al23 and Shaik et al30 However, More and Aarani27 observed that the elongated styloid process was more common on the right side in their study population. Ilgüy et al6 and Custodio et al31 observed no difference in the length of the styloid process when the sides were compared.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was in accordance with Bozkir et al,19 Vadgaonkar et al,22 Roopashri et al23 and Shaik et al30 However, More and Aarani27 observed that the elongated styloid process was more common on the right side in their study population. Ilgüy et al6 and Custodio et al31 observed no difference in the length of the styloid process when the sides were compared.…”
Section: Discussionmentioning
confidence: 97%
“…Many critical anatomic structures such as facial and hypoglossal nerves, occipital artery, internal jugular vein, internal carotid artery, and posterior belly of the digastric muscle are closely located to the SP and the stylohyoid ligament. [4567] The elongation of SP can frequently be encountered by calcification of stylohyoid and stylomandibular ligaments, being the potentially triggering factors to precipitate a series of symptoms such as foreign body sensation in the throat, pain on rotating the head, vertigo, dysphagia, odynophagia, facial pain, earache, headache, tinnitus, and trismus, resulting in Eagle syndrome. [4] However, majority of the cases are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Custodio et al [ 1 ], Vadgaonkar et al [ 2 ], Natsis et al [ 32 ], Sakaew et al [ 33 ] evaluated SP elongation on dry skulls in Brazilian, Indian, Greek and Thai populations, respectively; other studies, such as that conducted by Kursoglu et al [ 4 ] on Turkish, More and Asrani [ 26 ] on Indian, Shaik et al [ 31 ] on Saudian and Al-Khateeb et al [ 34 ] on Jordanian populations were performed based on panoramic radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The styloid process (SP) is a thin cylindrical bony structure that projects downward and forward from the inferior surface of the petrous temporal bone anteromedially to the stylomastoid foramen. It is located between the carotid arteries and presents the site of insertion of the stylohyoid, styloglossus, and stylopharyngeus muscles, as well as to the stylohyoid and stylomandibular ligaments [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%